New approach to soil management - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
TropSoils, one of the USA's ColIaborative Research Support Programs, was established in 1981 as a partnership between US universities, the OS Agency for International Development (USAID) and collaborative institutions in developing countries....